2018
DOI: 10.1177/0300060518795528
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron levels are an independent predictor of in-hospital mortality of critically ill patients: a retrospective, single-institution study

Abstract: Objective This study aimed to examine the relationship between serum iron levels and in-hospital mortality in critically ill patients. Methods We retrospectively studied 250 critically ill patients who received treatment at the intensive care unit between June 2015 and May 2017. Blood chemistry and hepatic and renal function were measured. Kaplan-Meier survival curves were plotted according to serum iron levels. Correlations between serum iron levels and other variables were analyzed. Results A total of 165 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Iron deficiency was highly prevalent in idiopathic pulmonary arterial hypertension, and the extent of iron deficiency was also related to hemodynamics [10]. The level of serum iron was thought to be an independent predictor of in-hospital mortality in critically ill patients [11]. We noted that patients with COVID-19 who died during hospitalization had markedly severe chest CT images and significantly lower serum iron levels compared with those who survived before and after treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Iron deficiency was highly prevalent in idiopathic pulmonary arterial hypertension, and the extent of iron deficiency was also related to hemodynamics [10]. The level of serum iron was thought to be an independent predictor of in-hospital mortality in critically ill patients [11]. We noted that patients with COVID-19 who died during hospitalization had markedly severe chest CT images and significantly lower serum iron levels compared with those who survived before and after treatment.…”
Section: Discussionmentioning
confidence: 90%
“…However, the renal function was normal in this study, which was inconsistent with that in a previous study. It has been reported that a decreased level of serum iron in patients with pneumonia is an independent risk factor for in-hospital death [17] . The mechanism may be related to the influence of pathogenic microorganism infection on iron uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Also, iron deficiency can affect immune system function and hypoxia sensing. Little is known about the potential role of disturbing iron homeostasis in COVID-19 [ 34 , 35 ]. An investigation on 50 COVID-19 patients has indicated most of them had extremely low levels of serum iron, which was defined as a predictor of mortality [ 34 ].…”
Section: The Role Of Hepcidin In Severity and Mortality Of Covid-19mentioning
confidence: 99%